Cluster analysis in early axial spondyloarthritis predicts poor outcome in the presence of peripheral articular manifestations - Costantino, Felicie; Aegerter, Philippe; Schett, Georg; De Craemer, Ann-Sophie; Molto, Anna; Van Den Bosch, Filip; Elewaut, Dirk; Breban, Maxime; D'Agostino, Maria-Antonietta (Rheumatology, 2021)
Objectives. To assess whether two cluster analysis-based axial SpA (axSpA) endotypes (A for purely axial; B for both axial and peripheral) are stable over time and are associated with different long-term disease outcomes.
CRIS-Team WoS Importer:2022-05-13